Nivel de conocimiento sobre salud bucal y hábitos de higiene oral en gestantes del IPRESS -3 Tupac Amaru Iquitos – 2023 - Amasifuen Shupingahua, Juanita Priscila (2024)
OBJECTIVE: To determine the level of knowledge about oral health and oral hygiene habits in pregnant women attending the public health facility in the year 2023. METHOD: Non-experimental, analytical, cross-sectional quantitative research was conducted. The study included 99 pregnant women selected from those attending IPRESS-3 Tupac Amaru from January to December 2023. A selfadministered questionnaire was provided to the pregnant women. RESULTS: Our findings revealed that 54.55% of the total pregnant women attending IPRESS-3 Tupac Amaru exhibited a good level of knowledge in oral health.Approximately half of the participants (49.99%) demonstrated high levels of oral hygiene habits.Furthermore, a statistically significant correlation was identified between a high level of knowledge in oral health and good oral hygiene habits; 70.73% of pregnant women with elevated knowledge exhibited commendable oral hygiene habits (p < 0.0001). CONCLUSIONS: A statistically significant relationship was identified between the level of knowledge about oral health and the oral hygiene habits of pregnant women attending IPRESS-3 Tupac Amaru. Regarding the association between the level of knowledge and the various dimensions of oral hygiene habits, it is noteworthy that the habit of visiting the dentist was the only one that did not show statistical significance.